Requirements Analysis of a Poverty Household Information System for Government Agency Officers in Nakhon Ratchasima Province - Popitikul, Chutrapee; Chimplee, Kanokporn (Journal of Applied Science and Innovation, 2026)
This study aimed to analyze the requirements of a poverty-household information system from the perspective of government officers and to develop the Sequential Mixed-Methods Requirements Analysis Framework (SMRAF) for e-government information system projects. The study was conducted in Nakhon Ratchasima Province, Thailand, using a sequential exploratory mixed-methods design (QUAL quan) involving 20 participants from 10 government agencies. The qualitative phase employed focus group discussions and thematic analysis to identify system requirements, while the quantitative phase utilized a five-point Likert-scale questionnaire and the MoSCoW prioritization framework to validate and prioritize the identified requirements. The findings revealed five major requirement categories: (1) system accessibility and usability, (2) data coverage and quality, (3) data deduplication, (4) reporting and analytical functions, and (5) system integration. Among these, data deduplication received the highest priority rating ( = 4.75, SD = 0.44) and was classified as a Must Have requirement. Participants from all agencies emphasized the recurring issue of identical households appearing across multiple databases, which negatively affected the accuracy and fairness of public assistance allocation. Quantitative findings confirmed the qualitative results for the first four categories and further revealed differences in digital literacy and system understanding among user groups regarding system integration requirements. This study provides a validated set of requirements for poverty-household information systems in the Thai context and proposes the SMRAF framework as a practical approach for requirements analysis in e-government information system projects involving stakeholders with varying levels of technological understanding.